Pitfalls of cold sustainability planning - Claudio Gambardella (Techne)
“Beyond all Limits: International Conference on Sustainability in Architecture, Planning, and Design” is the title of a conference resulting from the cooperation between three universities, namely Çankaya University of Ankara, the University of Campania “Luigi Vanvitelli”, and the University of Strathclyde in Glasgow (which replaced the University of Plymouth in 2021). The second edition, held in May 2022 at Officina Vanvitelli, located at the San Leucio Belvedere in San Leucio-Caserta, was organised by the Vanvitelli University, which assumed responsibility for the event. The conference aimed at exploring sustainability in ways that would reflect and contribute to the latest international approaches. The event covered the fields of architecture, planning, and design, and was framed within the context of the NEB (New European Bauhaus), launched by the European Commission in 2021 to promote the three pillars of Sustainability, Aesthetics, and Inclusion. The NEB initiative is an interdisciplinary and creative endeavour that aligns with the objectives of the European Green Deal, emphasising human-centred design and promoting a novel lifestyle paradigm where sustainability and style converge, thereby catalysing the green transition across various economic sectors, including construction, furniture, fashion and other domains of daily life.